General information about the operational properties of foam concrete as a modern energy-efficient building material (International conference on multidisciplinary science, 2025)
The thesis describes the characteristics of foam concrete as a perspective building material, attention to detail, its properties, economy and ecology. Indicated different brands of foam concrete, ix physical and mechanical properties. The importance of control over production processes to ensure the durability and stability of the material is emphasized. Despite numerous advantages, limitations of foam concrete have also been noted, such as low mechanical strength and shrinkage, which requires further research and improvements to improve its performance characteristics.